2006
DOI: 10.2113/gscanmin.44.2.323
|View full text |Cite
|
Sign up to set email alerts
|

Diamond From the Los Coquitos Area, Bolivar State, Venezuela

Abstract: C, of the Los Coquitos diamond vary from +0.4 to -20.5‰, compared with -3.2 to -28.7‰ in the Quebrada Grande diamond. In the Los Coquitos suite, mineral inclusions in diamond are characterized by a lower Ca content in garnet, wider compositional variations in pyroxene (mg in the range 0.683-0.849), and lower Fo component in olivine (mg in the range 0.926-0.932), compared to inclusions in diamond in the Quebrada Grande suite. Los Coquitos diamond shows greater depletion in LREE compared to Quebrada Grande diamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…It has an FeO content of 97 wt.%, with only 0.09 wt.% MgO, and Mg# = 0.2. It has been suggested that this wüstite might belong to the lowermost mantle (Kaminsky et al, 2006). The present study has identified other wüstite inclusions in diamond from the Juina area, Brazil.…”
Section: Carbonatitic Mineral Association In Diamondsupporting
confidence: 49%
“…It has an FeO content of 97 wt.%, with only 0.09 wt.% MgO, and Mg# = 0.2. It has been suggested that this wüstite might belong to the lowermost mantle (Kaminsky et al, 2006). The present study has identified other wüstite inclusions in diamond from the Juina area, Brazil.…”
Section: Carbonatitic Mineral Association In Diamondsupporting
confidence: 49%
“…Compositional features and associations of some grains of ferropericlase gave reasons to suggest their origin within the D" layer at the core -mantle boundary (Harte et al, 1999;Kaminsky et al, 2006). Recently one of diamond crystals from the Juina area in Brazil was found to contain carbonate and halide inclusions associated with wüstite + periclase association, presumably from the D" layer (Kaminsky et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%